Observation of strangeness enhancement with charmed mesons in high-multiplicity 𝑝⁢Pb collisions at √𝑠NN =8.16 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Langenbruch, Christoph; et al. (Physical review, 2024)
The production of prompt 𝐷+𝑠 and 𝐷+ mesons is measured by the LHCb experiment in proton-lead (𝑝⁢Pb) collisions in both the forward (1.5 <𝑦* <4.0) and backward (−5.0 <𝑦* <−2.5) rapidity regions at a nucleon-nucleon center-of-mass energy of √𝑠NN=8.16 TeV. The nuclear modification factors of both 𝐷+𝑠 and 𝐷+ mesons are determined as a function of transverse momentum, 𝑝T, and rapidity. In addition, the 𝐷+𝑠 to 𝐷+ cross section ratio is measured as a function of the primary charged particle multiplicity in the event. An enhanced 𝐷+𝑠 to 𝐷+ production in high-multiplicity events is observed for the whole measured 𝑝T range, in particular at low 𝑝T and backward rapidity, where the significance exceeds six standard deviations. This constitutes the first observation of strangeness enhancement in charm quark hadronization in high-multiplicity 𝑝⁢Pb collisions. The results are also qualitatively consistent with the presence of quark coalescence as an additional charm quark hadronization mechanism in high-multiplicity proton-lead collisions.
Veröffentlicht: 22. August 2024
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
*LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1076 weitere Personen]
Gesehen am 25.06.2025